Poverty, caring and older age - Argyle, Elaine (University of Sheffield, 2002)
Due to the high incidence of disability amongst their contemporaries, older people are likely to be involved in informal caring relationships. Due to the limited nature of post-retirement incomes, such carers are also likely to be relatively poor. In spite of this, little attention has been given to the role of older carers of disabled people or to the influence of poverty upon this role. It is therefore the purpose of this paper to help to redress this neglect by examining the influence of material circumstances on the role of older carers aged over sixty. With this aim in mind a sample of 34 older co-resident carers were asked a series of questions relating to their access to resources and their caring role.